Pengaruh Faktor Personal dan Organisasional pada Sikap Berbagi Pengetahuan Dosen Akuntansi (Studi Empiris di Jayapura) - Sesa, Pascalina V. S; Wonar, Klara; Simanjuntak, Aaron (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This research designed as causal research that investigates the influence of student attitudes on student knowledge sharing behavior and descriptive research using a quantitative approach. The research population was students at universities in Jayapura and the sample was selected using a purposive sampling technique. Quantitative data type with data source in the form of primary data was obtained through filling out questionnaires by respondents. Primary data in the form of questionnaires distributed to universities in Jayapura. The research sample was 61 accounting students. Hypothesis processing using SmartPLS by looking at outer model and inner model measurements. These findings indicate that accounting students' attitudes influence students' behavior in sharing knowledge. The results of this research are useful for lecturers, curriculum designers, and educational planners to consider appropriate steps to promote knowledge sharing activities and integrate them into academic activities. Keywords: knowledge sharing behaviour, intellectual capital, students, university.